A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 4 years ago
(4X)^2  (4X)^3
A: X^1
B:12X^1
C:16x^2  4X^3
D:16x^2  64X^3
anonymous
 4 years ago
(4X)^2  (4X)^3 A: X^1 B:12X^1 C:16x^2  4X^3 D:16x^2  64X^3

This Question is Closed

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0\[(4x)^2  (4x)^3 = (4x^2)(14x) = 16x^2(14x) = 16x^2  (16\times 4)x^3 = 16x^2  64x^3\]

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0sorry there is a little issue\[ (4x)^2−(4x)^3=(4x)^2(1−4x)\] the rest of what i wrote is right

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0Ha Can you explain that a little bit like how you got the one and started simplifying ? im kind of confused

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0\[(4x)^2  (4x)^3 = (4x)^2(14x)\] because (4x)^2 is common to both (4x)^2 and (4x)^3, since \[1\times (4x)^2 = (4x)^2,\] and \[(4x)\times (4x)^2 = (4x)^3.\] \[(4x)^2(14x) = 16x^2(14x)\] because (4x)^2 = (4^2)(x^2) = 16x^2. Now just multiply out.

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0\[\left( 4x ^{2} \right)=4^{2}x ^{2}=16x ^{2} \] in the same way \[\left( 4x ^{3} \right)=4^{3}x ^{3}=64x ^{3}\] substitute both of them u will get\[ 16x ^{2}64x ^{3}\] 16x square 64x cube

anonymous
 4 years ago
Best ResponseYou've already chosen the best response.0That makes sense guys thanks :)
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.